Application of Information Technology in Construction : A Case from Nepal - Aryal, Bindu; Chapagain, Devendra; Dhakal, Bhawani; Aryal, Binod (Apex Journal of Business and Management, 2023)
This study aimed to identify the functions of information technology (IT) in the development of the construction industry in Chitwan and Nawalparasi. The study utilized a 5-point Likert scale questionnaire survey administered to ten contractors and ten consultants in the area. The survey included remarks about how IT is used in the construction industry, and four areas of IT use in construction were established. The identified outcomes were evaluated using Relative Importance Index (RII) and Ranking. The study found that the operational level, design level, and official level of management were the three most important levels of management by the relative importance index analysis. The mobile phone, laptop, and desktop computer were the primary hardware devices utilized on-site, and Microsoft Office applications such as Excel, Project, PowerPoint, and Word were determined to be the most important applications used in site administration. The study concluded that IT is a critical tool for the administration and management of construction projects. The findings of this study are consistent with other research that highlights the importance of IT in the construction industry. Information technology is streamlining operations in the construction sector, improving construction quality and safety measures, and maximizing efficiency and reliance on data in construction. The adoption of data-driven technologies such as building information modeling (BIM) is transforming the construction industry. Modern technologies and construction software are helping to control the information and disseminate it so it can be available and useful to project teams. Overall, the use of IT in the construction industry is becoming increasingly important, and its benefits are clear.